Karakteristik Fisik, Kimia dan Kesukaan Katte Tong Mocaf-Terigu dengan Penambahan Bubuk Kunir Putih (Curcuma mangga Val.) dan Baking Powder - Nur Aisyah; Dwiyati Pujimulyani; Yuli Perwita Sari (Journal of Food and Agricultural Product, 2023)
Mocaf flour is a local food source that can be substituted in katte tong as a functional food. The addition of white saffron powder (Curcuma mangga Val.) which has high antioxidant activity is believed to be able to ward off free radicals. This study aims to produce katte tong mocaf products that contain antioxidant activity with variations in the addition of white saffron powder and baking powder and determine the effect on the physical, chemical, and level of liking of katte tong. This study used a 2-factorial completely randomized design (CRD), namely variations in the addition of 5, 10, and 15% white saffron powder and 1, 1.5, and 2 g of baking powder. The data obtained were tested statistically with Univariate Analysis of Variance (ANOVA), if there was a significant difference, it was tested with Duncan Multiple Range Test (DMRT) ?=0.05. The results showed that variations in the addition of white saffron powder and baking powder had a significant effect on the characteristics of physical, chemical, and level of liking of the resulting mocaf katte tong. Katte tong mocaf with the addition of 10% white saffron powder and 2% baking powder is a katte tong that is favored by panelists. The results of the analysis of the selected mocaf katte tong had a moisture content of 2.70%bb, protein 8.35%bb, antioxidant activity of the DPPH method 35.12%RSA, antioxidant activity of the FRAP method 6.53% mg E Ferro/g, and total phenols 14.02 mg GAE/g. Keywords: white saffron, antioxidant activity, baking powder, katte tong